Autobiografias transmasculinas e literatura social : gênero, memória e a leitura do outro na cultura trans - Neves, Benjamin de Almeida (2023)
This research proposes to investigate, rescue, and compare four national transmasculine people autobiographies: A queda para o alto (1982), by Anderson Herzer, Viagem solitária (2011), by João W. Nery, Eu Trans: a alça da bolsa, relatos de um transexual (2014), by Jordhan Lessa, and Missão Vencer! – Nós não nascemos para ser um nada (2021), also written by Jordhan Lessa. Besides relating them to the concepts of social literature (CANDIDO, 2004), memory (RICOEUR, 2018), trans studies (STRYKER, 2006), female masculinity (HALBERSTAM, 1998) and the recent Brazilian movement of transmasculine people, this thesis also seeks to add reflections and problematize some categories – which I identified as common in the four works – and which are also significant for thinking about the perspectives of the lives of different transmasculinities: health and employability. Throughout this work, I sometimes choose to make use of my own subjectivities as an activist with the aim of contributing to the representativeness and visibility of transmasculine culture, such as social literature and trans epistemology.